Nano-scale VLSI clock routing module based on useful-skew tree algorithm - Eik Wee, Chew; Heng Sun, Ch'ng; Shaikh-Husin, Nasir; Hani, Mohamed Khalil (School of Postgraduate Studies, UTM, 2006)
Clock routing is critical in nano-scale VLSI circuit design. Clock routing needs to be precise to minimize circuit delay. Clock signals are strongly affected by technology scaling, the long global interconnect lines become highly resistive as line dimensions are decreased. The control of clock skew can also severely limit the maximum performance of the entire system and create catastrophic race conditions in which an incorrect data signal may latch within a register. Thus, we propose a clock routing synthesis module that applies non-zero skew (or called useful-skew) method to reduce the system-wide minimum clock period to improve the performance of synchronous digital circuit. We implemented Useful-Skew Tree (UST) algorithm which is based on the deferred-merge embedding (DME) paradigm, as the clock layout synthesis engine. The synthesis module is integrated with the UTM in-house design graph accelerator to enhance the computation performance. The novel contribution of this work is clock skew scheduling is performed simultaneously with clock tree routing. This way, the computation result of proposed synthesis module can generate a clock signal distribution routing path with minimum wire length and, ensures the reliability of data synchronization for nano-scale VLSI design.